Identification Of Sub-Surface Rock Structures In The Banyu Biru Hot Springs Area Using The Gravity Method (UNIVERISTAS PGRI MADIUN, 2024)
One of the geothermal manifestations in Nganjuk is the Banyu Biru hot spring in Gondangwetan Village, Jatikalen District, Nganjuk regency. This hot spring was discovered by accident when drilling a well to be used as a rice field flow, but the water that came out was hot water with a temperature of 37 oC at a depth of 250-300 m. This study aims to determine local anomaly patterns and lithological structures of subsurface rocks in the Jatikalen hot spring area. The research method used is the gravity method based on GGMPlus satellite data obtained as many as 100 data with a distance of 200 m between points. Based on the qualitative analysis of the local anomaly contours, the low anomaly was -2.6 mGal to -0.8 mGal, the moderate anomaly was -0.6 mGal to 2.2 mGal, and the high anomaly was 0.6 mGal – 2.2 mGal. Quantitative interpretation with the results of the cross-sectional model resulted in 5 layers of topsoil with a density value of 1.2 grams/cm3. In the second layer is alluvium in the form of gravel, gravel, sand with a density of 1.7 grams/cm3. The third layer is tuffaceous clay with a density of 2 grams/cm3 and the fourth layer is calcareous tuff with a density value of 2.67 grams/cm3. While the last in the fifth layer is breccia rock with a density value of 3 grams/cm3.